Cost‐Effectiveness of LDL‐C Lowering With Evolocumab in Patients With High Cardiovascular Risk in the United States. Issue 6 (19th April 2016) - Gandra, Shravanthi R.; Villa, Guillermo; Fonarow, Gregg C.; Lothgren, Mickael; Lindgren, Peter; Somaratne, Ransi; van Hout, Ben
ABSTRACT: Randomized trials have shown marked reductions in low‐density lipoprotein cholesterol (LDL‐C), a risk factor for cardiovascular disease (CVD), when evolocumab is administered. We hypothesized that evolocumab added to standard of care (SOC) vs SOC alone is cost‐effective in the treatment of patients with heterozygous familial hypercholesterolemia (HeFH) or atherosclerotic CVD (ASCVD) with or without statin intolerance and LDL‐C >100 mg/dL. Using a Markov cohort state transition model, primary and recurrent CVD event rates were predicted considering population‐specific trial‐based mean risk factors and calibrated against observed rates in the real world. The LDL‐C–lowering effect from population‐specific phase 3 randomized studies for evolocumab was used together with estimated LDL‐C–lowering effect on CVD event rates per 38.67‐mg/dL LDL‐C lowering from a statin‐trial meta‐analysis. Costs and utilities were included from published sources. Evolocumab treatment was associated with both increased cost and improved quality‐adjusted life‐years (QALY): HeFH (incremental cost: US$153 289, incremental QALY: 2.02, incremental cost‐effectiveness ratio: US$75 863/QALY); ASCVD (US$158 307, 1.12, US$141 699/QALY); and ASCVD with statin intolerance (US$136 903, 1.36, US$100 309/QALY). Evolocumab met both the American College of Cardiology/American Heart Association (ACC/AHA) and World Health Organization (WHO) thresholds in each population evaluated. Sensitivity and scenario analyses confirmed that model results were robust to changes in model parameters. Among patients with HeFH and ASCVD with or without statin intolerance, evolocumab added to SOC may provide a cost‐effective treatment option for lowering LDL‐C using ACC/AHA intermediate/high value and WHO cost‐effectiveness thresholds. More definitive information on the clinical and economic value of evolocumab will be available from the forthcoming CVD outcomes study.